Decrees Nos. 535, 536, and 537 for the year 2015 concerning Egyptian standard specifications / Egypt. Ministry of industry, trade, and small & medium projects ; Translated by The middle east library for economic services. - Egypt. Ministry of industry, trade, and small & medium projects; The middle east library for economic services, translator. (2025)
Serial No. 37/2015